Strategi Guru dalam Mewujudkan Pembelajaran Interaktif Inspiratif dan Menyenangkan untuk Meningkatkan Prestasi Belajar PAI di SMPN 1 Gondang - Lailatul Mubarokah (Scidac Plus, 2022)
This study focuses on the ways in which PAI teachers plan learning, carry out teaching and learning activities in class and the learning outcomes to improve student learning achievement at Gondang 1 Junior High School. This study uses qualitative research. Data collection was carried out by means of participant observation, in-depth interviews and documentation. The validity of the data is obtained by triangulation techniques. The data analysis model includes analysis of individual sites. The results show that the way PAI teachers plan inspirational and fun interactive learning in Gondang 1 Junior High School is to prepare a plan for teaching and learning activities. In this case the teacher makes a Learning Implementation Plan (RPP), learns the material then develops it, prepares appropriate learning media to achieve learning objectives and applies strategies in teaching and learning activities. The whole thing is made by considering the condition of students. The way PAI teachers carry out inspirational and fun interactive learning to improve student achievement in PAI. The method used by PAI teachers turns out to have significant results in improving the achievement of students, especially in Islamic Religious Education subjects. This can be seen from the list of values that consists of knowledge assessments, and skill’s assessments, which are skills that show good grades. In addition, non-academic achievements in the religious field were also quite satisfying, namely winning the Adhan, MTQ, and tahfidz.